The Adverse Effects of Prenatal METH Exposure on the Offspring: A Review - Li, Jia-Hao; Liu, Jia-Li; Zhang, Kai-Kai; Chen, Li-Jian; Xu, Jing-Tao; Xie, Xiao-Li (Frontiers in Pharmacology, 2021)
Abuse of methamphetamine (METH), an illicit psychostimulant, is a growing public health issue. METH abuse during pregnancy is on the rise due to its stimulant, anorectic, and hallucinogenic properties. METH can lead to multiple organ toxicity in adults, including neurotoxicity, cardiovascular toxicity, and hepatotoxicity. It can also cross the placental barrier and have long-lasting effects on the fetus. This review summarizes neurotoxicity, cardiovascular toxicity, hepatotoxicity, toxicity in other organs, and biomonitoring of prenatal METH exposure, as well as the possible emergence of sensitization associated with METH. We proposed the importance of gut microbiota in studying prenatal METH exposure. There is rising evidence of the adverse effects of METH exposure during pregnancy, which are of significant concern.